Letter from Albert Harnickle to James Curtis Booth - Harnickel, Albert (1860)
Albert Harnickle writes asking to supply nickel to the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; Nickel; United States Mint; Mint of the United States